2017
DOI: 10.1007/s11663-016-0901-9
|View full text |Cite
|
Sign up to set email alerts
|

Mold Simulator Study of Heat Transfer Phenomenon During the Initial Solidification in Continuous Casting Mold

Abstract: In this paper, mold simulator trials were firstly carried out to study the phenomena of the initial shell solidification of molten steel and the heat transfer across the initial shell to the infiltrated mold/shell slag film and mold. Second, a one-dimensional inverse heat transfer problem for solidification (1DITPS) was built to determine the temperature distribution and the heat transfer behavior through the solidifying shell from the measured shell thickness. Third, the mold wall temperature field was recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 68 publications
0
42
0
Order By: Relevance
“…cess A one-Dimensional Inverse Heat Transfer Problem for Solidification (1DITPS) mathematic model was adopted to determine the temperature distribution of the solidifying shell from the measured shell thickness. 33) In Fig. 1(b), the initial temperature of steel is melt temperature (Table 3), and the boundary conditions are set as heat flux q(t) = 0 at the shell surface (x' = 0) side and is insulated at x' = l side where the liquid steel is in contact with the wall of furnace (MgO).…”
Section: Determination Of Initial Shell Solidification Pro-mentioning
confidence: 99%
See 2 more Smart Citations
“…cess A one-Dimensional Inverse Heat Transfer Problem for Solidification (1DITPS) mathematic model was adopted to determine the temperature distribution of the solidifying shell from the measured shell thickness. 33) In Fig. 1(b), the initial temperature of steel is melt temperature (Table 3), and the boundary conditions are set as heat flux q(t) = 0 at the shell surface (x' = 0) side and is insulated at x' = l side where the liquid steel is in contact with the wall of furnace (MgO).…”
Section: Determination Of Initial Shell Solidification Pro-mentioning
confidence: 99%
“…The 1DITPS mathematic model is capable of determined the heat-transfer process of solidifying shell from the measured shell thickness and shows a good anti-interference ability of inverse results to the thickness measurement noise, and the detailed description of this mathematic model has been well illustrated in our previous study. 33) 3. Resuilts and Discussion…”
Section: Determination Of Initial Shell Solidification Pro-mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the strand surface defects, such as cracks, oscillation marks, ripples, depression even breakout, originate in the mold region with close relationship to shell initial growth. [1][2][3][4][5][6][7][8][9][10] Therefore, many methods to measure the shell thickness have been proposed. In the 1980s, Brimacombe [1] and Suzuki [2] added a radioactive tracer(198Au) to the liquid pool during steel casting to reveal the shape of solid shell.…”
Section: Introductionmentioning
confidence: 99%
“…Using numerical methods, Thomas and Mills et al [16][17][18] confirmed that the formation of a hook-type OM results from the overflow of the liquid steel over the partially solidifying meniscus; the mold oscillation and narrow width of the liquid mold flux film between the mold and shell make numerical calculations extremely difficult. Recent high-temperature experiments performed by Badri and Wang confirmed that the formation of hook-type OMs is associated with partial solidification of the meniscus; in addition, the partial solidification of the meniscus was shown to be accompanied by an increase in the mold heat flux in the meniscus area [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%